"The Lesser of Two Weevils": British victualling organization in the long eighteenth century. (7th November 2017) - Allen, Douglas W
Abstract: The British Navy's Victualling Board was created in 1683 after more than a century of victual attempts rife with corruption, incompetence, and inedibles; and ended in 1832 with the creation of the modern Admiralty. Historians are unanimous that the Victualling Board was an immediate and continuous improvement, daily feeding tens of thousands across the globe. On the other hand, to the modern eye, many aspects of the Victualling Board appear odd and costly—excessive inventories, unpassed accounts, charge and discharge accounting, in-house production, mutual surveillance, and excessive punishments. Here these two observations are reconciled. I argue that the Board's organization was a clever response to pre-modern transaction cost problems; that is, the Board was designed to create compatible incentives subject to the measurement constraints of the time.